Analysis Of The Business Feasibility Studi Of The Eldest Putri Cracker Factory In Mundam Marap Village, Mukomuko Regency - Meta Novita; Tito Irwanto; Dewi Harwini (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the amount of cost, income, profit, and the level of business feasibility of the cracker production, as well as to identify the problems faced in managing the business. According to Kasmir and Jakfar, a feasibility study is essential to assess the extent to which a business can provide benefits to investors and related stakeholders. A feasibility study is a crucial stage that cannot be overlooked, as it serves to compare the costs incurred with the benefits obtained. This research employs a qualitative descriptive method with an approach based on actual field conditions. Data were collected through observation and interviews. The financial aspect analysis was conducted using the Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI) methods. The object of this study is the Putri Sulung Cracker Factory, established in 2009 by Mr. Sudarso and managed independently without involving employees. The main objective of establishing this business was to support the family’s economy and take advantage of market opportunities for traditional snack products. The analysis results show that the PP value in 2023 was 3.753 years and decreased to 2.496 years in 2024, indicating that the investment return period is relatively long. The NPV value was IDR 230,516,003 (positive), PI was 7.683, and IRR reached 15.02. These three indicators demonstrate that the business provides benefits to investors and has growth potential. Based on these results, it can be concluded that the Putri Sulung Cracker Factory business is feasible to operate and has a high potential for financial profitability.